The lateral supraorbital approach, doable and cosmetic access to anterior skull base - Ahmed Abdelaziz Elsharkawy; Essam Ahmed Abdelhameed (Egyptian Journal of Neurosurgery, 2020)
Abstract Background The anterior skull base region can be reached through multiple corridors. The most frequently used are the pterional, bifrontal, unifrontal, and orbitozygomatic approaches. These approaches are more extensive and time consuming. The lateral supraorbital approach is a less extensive frontal modification of the classic pterional approach designed to manage tumors and aneurysms of this region. Objective To evaluate efficacy, safety, and cosmetic results of the lateral supraorbital approach and to present some tricks to have an easy access to different pathologies at the anterior skull base through this approach. Methods Analysis of 50 operations for anterior skull base pathologies, vascular and neoplastic, made through the lateral supraorbital approach in Neurosurgery Department, Tanta University Hospitals between January 2013 and April 2017. The basic steps in performing the procedure are described. Special tricks required in individual cases and how to identify their need from preoperative images are discussed. Results We operated on 50 patients having 34 neoplastic and 16 vascular lesions. The mean incision length was 11 cm, mean bone flap size was 3.5 × 5.4 cm, and mean craniotomy time was 20 min. All patients were satisfied with their scars; there were no limitations to this approach regarding nature or size of the lesion. We had 8 morbidities (4 transient and 4 permanent) and 2 mortalities; all morbidities and mortalities were not related to the approach. Conclusion The lateral supraorbital approach is simple, fast, and effective corridor to anterior skull base pathologies without significant morbidities or mortalities related to the approach.